Hierarchical Self‐Assembly of Peptides and its Applications in Bionanotechnology. Issue 14 (19th July 2019) - Gerbelli, Barbara B.; Vassiliades, Sandra V.; Rojas, Jose E. U.; Pelin, Juliane N. B. D.; Mancini, Rodrigo S. N.; Pereira, Wallace S. G.; Aguilar, Andrea M.; Venanzi, Mariano; Cavalieri, Francesca; Giuntini, Francesca; Alves, Wendel A.
Abstract : Front Cover : In article number1900085 by Wendel A. Alves and co‐workers, the self‐assembly properties of peptide nanomaterials in relation to their design and composition are surveyed. It is emphasized how environmental conditions can influence the morphology of peptide nanostructures, and how this dependence can be suitably exploited for the design of stimuli‐responsive systems.